Analisis Variasi Temperatur Aktivasi Terhadap Daya Serap Arang Aktif Tandan Aren (Arenga Pinnata Merr) Dengan Agen Aktivasi Potassium Silicate(K2SiO3) - Azam, Muhammad; Anas, Muhammad; Erniwati, Erniwati (Jurusan Pendidikan Fisika, 2020)
This study aims to determine the effect of variation of activation temperature of activated carbon from sugar palm bunches of chemically activatied with the activation agent of potassium silicate (K2SiO3) on the adsorption capacity of iodine and methylene blue. Activated carbon from bunches of sugar palmacquired in four steps: preparationsteps, carbonizationstepsusing the pyrolysis reactor with temperature of 300 oC - 400 oC for 8 hours and chemical activation using of potassium silicate (K2SiO3) activator in weight ratio of 2: 1 and physical activation using the electric furnace for 30 minutes with temperature variation of600 oC, 650 oC, 700 oC, 750 oC and 800 oC. The iodine and methyleneblue adsorption testedby Titrimetric method and Spectrophotometry methodrespectively. The results of the adsorption of iodine and methylene blue activated carbon from sugar palm bunches increased from 240.55 mg/g and 63.14 mg/g at a temperature of 600 oC to achieve the highest adsorption capacity of 325.80 mg/g and 73.59 mg/g at temperature of 700 oC and decreased by 257.54 mg/g and 52.03 mg/g at a temperature of 800 oCrespectively.However, it does not meet to Indonesia standard (Standard Nasional Indonesia/SNI), which is 750 mg/g and 120 mg/g respectively.